First isolation of a VIM-producing Klebsiella pneumoniae from a seven-year-old child in Venezuela - Daniel Marcano,1 Fernando Pasterán,2 Melina Rapoport,2 Diego Faccone,2 Carmen Ugarte,1 Nuris Salgado,1, Daisy Payares,1 Enza Spadola,1 Yoanna López,3 Graciela Maggi,3 Marcelo Galas,2 Damarys Sánchez.1 (The Journal of Infection in Developing Countries, 2008)
Background: VIM-type metallo-betalactamases (MBLs) exhibit hydrolytic activity against most betalactam antibiotics, including carbapenems. So far, VIM-type-producing Klebsiella pneumoniae isolates had not been reported in Latin America. Methodology: In July 2005, a carbapenem-resistant Klebsiella pneumoniae was isolated from a urine sample collected from a 7-year-old girl hospitalized at the Hospital de Niños "J. M. de los Ríos" in Caracas, Venezuela. This strain was identified using conventional biochemical tests. The susceptibility analysis was conducted by disk diffusion, and MICs for Imipenem and Meropenem were performed by agar dilution. For the phenotypic detection of MBL we used the Imipenem-EDTA/SMA double-disk diffusion method. The hydrolytic activity against carbapenems was determined by the Masuda microbiological method. Purified protein was subjected to isoelectric focusing (IEF). Detection of antimicrobial resistance genes was performed by PCR amplification with specific VIM primers. Results: The strain showed resistance to most betalactam antibiotics, quinolones and amynoglicosides, but remained susceptible to Aztreonam and Cefepime. The use of phenotypic and microbiological methods detected the presence of a metallobetalactamase. By IEF we visualized three bands at pI 5.4, 7.6 and 7.9, corresponding to reduced-spectrum betalactamases, and a band at pI 5.8 that corresponded to the metallobetalactamase. PCR screening of bla genes revealed the presence of blaVIM, with an amplicon of 261 bp. Conclusions: This is the first report of a MBL-mediated carbapenem-resistant Klebsiella pneumoniae in Latin America, which constitutes a public health concern in our region since their transference to other microorganisms with multiple antibiotic resistance mechanisms will increase the antimicrobial resistance problem.